Multidisciplinary Management of Lateral Skull Base Paragangliomas: A 20-Year Experience - Cleere, Eoin F.; Mc Loughlin, Laura; McArdle, Orla; Fitzpatrick, David; Looby, Seamus; Rawluk, D.; Javadpour, Mohsen; McConn-Walsh, Rory (Journal of Neurological Surgery Part B: Skull Base, 2023)
Objectives Paragangliomas of the lateral skull base are rare, largely benign, neuroendocrine tumors. Little evidence exists to support clinicians in the management of these tumors. The present study evaluates considerations in the multidisciplinary workup and management of paragangliomas affecting the lateral skull base.Methods A STrengthening the Reporting of OBservational studies in Epidemiology (STROBE) checklist compliant retrospective review of adult patients with lateral skull base paragangliomas over 20 years (2002–2021) was performed. Patient and tumor data were collected from patient health care records.Results Seventy patients were identified including 21 (30.0%) males and 49 (70.0%) females. The mean length of follow-up was 87.3 months (range: 12–239 months). Twenty-nine (41.4%) patients had Fisch A or B tumors. Overall, 57 patients (81.4%) were offered treatment upfront, with 13 patients (18.6%) initially undergoing active surveillance. Younger age and reduced American Society of Anesthesiologists (ASA) grade was significantly associated with a decision to offer treatment at presentation (both p = 0.03), while all patients with succinate dehydrogenase (SDH) mutations (n = 10) and tumor secretion (n = 4) were offered treatment. Patients with Fisch A/B tumors (p = 0.01), cranial neuropathies (p = 0.01), and smaller tumors (p = 0.01) were more likely to undergo surgical resection. At the time of the last follow-up, the proportion of patients with a cranial neuropathy was notably lower in the observation (3/12, 25.0%) and radiotherapy (1/6, 16.7%) groups.Conclusion In our series, younger, fitter patients with SDH mutations, cranial neuropathies, or tumor secretion were more likely to be offered upfront treatment. There was a low incidence of new cranial neuropathy in the patients selected for observation during long-term follow-up.
Keywords: skull base; paraganglioma; multidisciplinary; surgery; stereotactic radiosurgery